Adaptive dynamic programming-based decentralised control for large-scale nonlinear systems subject to mismatched interconnections with unknown time-delay - Wu, Qiuye; Zhao, Bo; Liu, Derong (International journal of systems science, 2020)
This paper addresses decentralised optimal control problems for large-scale nonlinear systems subject to mismatched interconnections with unknown time-delay by adaptive dynamic programming. To eliminate the effects of mismatched interconnections with unknown time-delay, a novel local value function is constructed to transform the decentralised control problem into an optimal control problem. A local robust observer is established to identify the bound of the unknown interconnections. Then, based on the observer-critic architecture, the decentralised optimal control policy is achieved by solving local Hamiltonian-Jacobi-Bellman equation via local policy iteration algorithm. The stability of the closed-loop large-scale nonlinear system is guaranteed to be uniformly ultimately bounded by implementing a set of decentralised control policies. Simulation examples demonstrate the effectiveness of the proposed scheme.